Asymptomatic multifocal avascular necrosis, a commonly overlooked finding in patients with systemic lupus erythematosus - Forough Nadi; Esmat Abdollahpour; Babak Fallahi; Leila Aghaghazvini; Majid Alikhani; Mohammad Nejadhosseinian; Seyedeh Tahereh Faezi (BMC Rheumatology)
Abstract Background In patients with Systemic lupus erythematosus (SLE), osteonecrosis of various joints is a debilitating complication associated with the disease and its treatment, in which a considerable proportion of osteonecrosis may be asymptomatic. Recognizing the crucial role of early and timely detection, as well as appropriate management of asymptomatic osteonecrosis, in preventing joint destruction, we conducted a study to evaluate the prevalence of asymptomatic osteonecrosis in SLE patients who have already been diagnosed with symptomatic osteonecrosis. Additionally, we aimed to examine the relationship between proposed risk factors of osteonecrosis and the development of asymptomatic osteonecrosis. Methods In this cross-sectional study, Patients with recently diagnosed symptomatic osteonecrosis of at least one joint were selected by reviewing data from the digital medical record system of the Rheumatology Research Center. The patients underwent three-phase Single Photon Emission Computed Tomography (SPECT) bone scintigraphy to screen for other asymptomatic osteonecrotic joints. MRI was subsequently performed on the asymptomatic osteonecrotic sites for further diagnostic confirmation. The study evaluated the prevalence of asymptomatic osteonecrosis, the extent of joint involvement, the specific locations of osteonecrosis, the most commonly affected joints, and the risk factors for asymptomatic osteonecrosis. Results Eight out of the 17 patients (47%) who participated in our research were found to have asymptomatic osteonecrosis. The most commonly affected joint without symptoms was the left knee (25%), while the most frequently affected joint with symptoms was the left hip (23.07%). The only statistically significant difference observed between patients with and without asymptomatic osteonecrosis in this study was the age at which the disease first appeared (p = 0.046) and this age was higher among patients with asymptomatic osteonecrosis. Conclusions Our research provides further evidence of the high incidence of asymptomatic osteonecrosis in individuals with SLE due to the nature of the disease and the frequent use of high-dose corticosteroids. It underscores the importance of early detection through whole-body SPECT bone scintigraphy and MRI, as well as prompt intervention in order to avert the incapacitating effects of osteonecrosis.